Construire les hommes comme des victimes irresponsables - Étienne Lefort (Glad!)
This article compares the arguments of several associations defending fathers’ rights in order to study the rhetorics of the most active part of the French masculinist movement. By studying together the writings of an association presenting itself as a study group and interviews made with activists from other associations holding group meetings, this paper reveals the common ground in the discursive strategies of the different actors of this movement. The appropriation of the question of sex equality and the criticism of the family justice system are means to convey an anti-feminist discourse which fuels a dynamic of individual and collective unaccountability for men.